PELATIHAN GURU TK DALAM MENGHADAPI PROSES PEMBELAJARAN DARING DAN LURING TERBATAS DI MASA PANDEMI - Soetam Rizky Wicaksono; Felik Sad Windu Wisnu Broto; Melany Melany (Gapenas Publisher, 2022)
TKK Santa Maria 3 is formed in the 1980s under the auspices of the Surabaya Dharma Putri Association Foundation. One of the difficulties faced emerged after the Covid-19 pandemic occurred online learning. In addition to facilities and infrastructure, the existing human resources at the TKK Santa Maria 3 Malang school still do not have adequate provisions for the implementation of online learning. Therefore, the service team from Ma Chung University held training for kindergarten teachers, especially at TKK Santa Maria 3 Malang, during the pandemic and post-pandemic, in order to be better prepared in the online learning process. This hybrid, offline and online activity is carried out in early 2021 with the hope that teachers can be more confident and apply better creativity in carrying out online learning. In practice, there are three main materials based on brainstorming and initial situation analysis, namely: (1) seeking information or seeking information, (2) blended learning and (3) acquisition of information or acquiring information that has been obtained for dissemination to students. The results of these activities can be carried out well, but after the evaluation is complete, there are several things that still need further explanation and adaptation in the post-pandemic PTMT period in 2022. So it is recommended that the team should hold similar activities again by adding more material which can bring teachers to adapt to the new conditions at current condition